Genomic structure and sequence analysis of Lucilia cuprina HSP90 gene - Janardhan reddy, P. V.; Tiwari, P. K. (Cellular and Molecular Biology, 2011)
The HSP90 family is one of the highly conserved chaperone families, varying between eubacteria to higher vertebrates. The HSP90 protein has been assigned different functions including thermal protection, but having major role in development. The present study is a detailed analysis of the structural characteristics of hsp90 gene (lchsp90) of sheep blowfly, Lucilia cuprina. The gene isolated by PCR revealed absence of intron. The nucleic acid and amino acid comparison revealed significant level of sequence similarity among species of various taxa. Significantly, the analysis of the amino acid sequence revealed that the HSP90 of L. cuprina belongs to hsp90Î² class.